Risk factors for postoperative wound complications after extremity soft tissue sarcoma resection: A systematic review and meta-analyses. Issue 9 (September 2019) - Slump, Jelena; Bastiaannet, Esther; Halka, Anastassi; Hoekstra, Harald J.; Ferguson, Peter C.; Wunder, Jay S.; Hofer, Stefan O.P.; O'Neill, Anne C.
Abstract: Introduction: Advancements in imaging, surgical, and radiation techniques have made resection of larger and more extensive extremity soft tissue sarcomas (ESTS) possible but with the potential for high complication rates. This study summarizes complication and reoperation rates associated with resection of ESTS and reviews predictors for wound complications. Methods: A systematic review of the literature on ESTS in adults was undertaken from the four databases MEDLINE, Embase, MEDLINE In-Process & Other Non-Indexed Citations, and the Cochrane Central Register of Controlled Trials (CCRCT). Meta-analyses of the complications, reoperations, and risk factors were performed. Results: In the twenty-one studies included, there was an overall wound complication rate of 30.2% (95% CI 26.56–33.47) and a reoperation rate of 13.37% (95% CI 10.21–16.52) in 5628 patients. Individual studies reported that older patient age, obesity, smoking, diabetes, large tumor size, tumor site, and preoperative radiotherapy were associated with adverse outcomes. Tumors of the lower limb, diabetes, smoking, obesity, and radiation were identified as independent predictors of wound complications in meta-analysis. A high level of heterogeneity between studies limited pooled analysis for many variables. Conclusions: Despite advancements in the treatment of ESTS, postoperative complication rates remain high. Awareness of the risk factors for wound complications, especially those that may be modifiable, is essential to decrease postoperative morbidities in these patients to improve treatment outcomes and quality of life.